COMPARISON OF METHOD WORK IMPLEMENTATION IMPROVEMENT OF SLOPE STABILITY IN TERMS OF COST AND TIME - Irriene Indah Susanti; Anis Eka Aprianti (Neutron, 2020)
Rampa street - Poriaha / Mungkur (WINRIP) is one location that has a slope angle on its slopes prone to landslides, causing damage to some roads. Based on these conditions, the Ministry PUPR slope handling project launched on this road. In practical improvements slope stability was conducted using three methods: manlift, hanging platforms and scaffolding. All three methods have their advantages and disadvantages in terms of both cost and time. To obtain the results of the comparison of cost and time to do the direct observation and study of literature, the comparative results obtained on the cost and time to get the method implementation in accordance with needs. From the three methods, the lowest cost and the fastest duration of the results implementation method using manlift with cost of Rp 1,557,623,470 and duration of work 29 days